Blood glucose responses in humans mirror lactate responses for individual anaerobic threshold and for lactate minimum in track tests - Simoes, H. G.; Campbell, CSG; Kokubun, Eduardo [UNESP]; Denadai, B. S.; Baldissera, V (Springer, 1999)
The equilibrium point between blood lactate production and removal (La-min(-)) and the individual anaerobic threshold (IAT) protocols have been used to evaluate exercise. During progressive exercise, blood lactate [La-](b), catecholamine and cortisol concentrations, show exponential increases at upper anaerobic threshold intensities. Since these hormones enhance blood glucose concentrations [Glc](b), this study investigated the [Glc] and [La-](b) responses during incremental tests and the possibility of considering the individual glucose threshold (IGT) and glucose minimum;(Glc(min)) in addition to IAT and La-min(-) in evaluating exercise. A group of 15 male endurance runners ran in four tests on the track 3000 m run (v(3km)); IAT and IGT- 8 x 800 m runs at velocities between 84% and 102% of v(3km); La-min(-) and Glc(min) - after lactic acidosis induced by a 500-m sprint, the subjects ran 8 x 800 m at intensities between 87% and 97% of v(3km); endurance test (ET)- 30 min at the velocity of IAT. Capillary blood (25 mu l) was collected for [La-](b) and [Glc](b) measurements. The TAT and IGT were determined by [La-](b) and [Glc](b) kinetics during the second test. The La-min(-) and Glc(min) were determined considering the lowest [La-] and [Glc](b) during the third test. No differences were observed (P < 0.05) and high correlations were obtained between the velocities at IAT [283 (SD 19) and IGT 281 (SD 21)m. min(-1); r = 0.096; P < 0.001] and between La,, [285 (SD 21)] and Glc(min) [287 (SD 20) m. min(-1) = 0.77; P < 0.05]. During ET, the [La-](b) reached 5.0 (SD 1.1) and 5.3 (SD 1.0) mmol 1(-1) at 20 and 30 min, respectively (P > 0.05). We concluded that for these subjects it was possible to evaluate the aerobic capacity by IGT and Glc(min), as well as by IAT and La-min(-).
Keywords: individual anaerobic threshold; lactate minimum; individual glucose threshold; glucose minimum; aerobic capacity evaluation